Asian dust observed during KORUS-AQ facilitates the uptake and incorporation of soluble pollutants during transport to South Korea. (1st March 2020) - Heim, E.W.; Dibb, J.; Scheuer, E.; Jost, P. Campuzano; Nault, B.A.; Jimenez, J.L.; Peterson, D.; Knote, C.; Fenn, M.; Hair, J.; Beyersdorf, A.J.; Corr, C.; et al.
Abstract: The air quality of South Korea was the focus of the NASA/NIER KORean -United States Air Quality (KORUS-AQ) mission of 2016. KORUS-AQ was planned for the period after the spring peak in outbreaks of Asian dust. Regardless of this strategic planning, quantifiable dust was still observed via instrumentation on the NASA DC-8 in early May. A novel analysis of supermicron dust and associated supermicron ionic relationships was completed using two size dependent instruments. This supermicron dust provided surface area for heterogeneous chemistry between CaCO3, the gases HNO3, NO2, and SO2, and particulate (NH4 )2 SO4 . Uptake of the pollutant gases is greatly enhanced by formation of an aqueous layer on the surface of the dust particles. More water is attracted to particles where uptake of HNO3 has replaced surface CaCO3 with Ca(NO3 )2 generating a dynamic aqueous layer on the dust particle. We propose that particulate (NH4 )2 SO4 coagulated with dust to form (NH4 )2 Ca(SO4 )2 on the particle surface, which rapidly formed CaSO4 and NH4 + in a Ca(NO3 )2 facilitated aqueous layer. A conceptual model is proposed to explain these dust uptake chemical processes. We define the nanoequivalent concentration of supermicron SO4 2− plus NO3 − over the nanoequivalent concentration of supermicron NH4 + plus Ca 2+ as the Dust Pollution Index (DPI), used to quantify the extent to which carbonate dust has been modified. DPI values range from 0 (pure dust) to 1 (completely reacted); thus, it represents the conversion of CaCO3 into secondary salts. This mechanism should be used to better predict chemical dynamics in atmospheric models while also helping to further explain the importance of dust and secondary coating on cloud formation processes and dust optical properties. Air masses containing dust that traversed industrial China while mixing with polluted southern air had significantly higher DPI values (average = 0.82, 1σ = 0.10) compared to air masses that limited interaction with such pollution (average = 0.51, 1σ = 0.13). Highlights: Supermicron dust collected during KORUS-AQ was chemically modified during transport, taking up HNO3 and (NH4 )2 SO4 . (NH4 )2 SO4 particles coagulated with dust while gas phase HNO3 reacted and modified the dust to be hygroscopic. A conceptual model and the Dust Pollution Index are proposed to explain these uptake mechanisms.